Analysis of Taxpayer Compliance Level in Rural and Urban Land and Building Tax Revenue (PBB-P2) in Kertajati District, Majalengka Regency - Lia Amalia (Yayasan Mentari Madani, 2023)
The level of compliance of taxpayers determines the level of achievement of the Realization of Land and Building Taxes in Rural and Urban Areas. The purpose of the research carried out is to determine the level of tax compliance in the receipt of Land and Building Taxes in Rural and Urban Areas in Kertajati District; what factors influence the level of tax compliance in Kertajati Subdistrict. The author uses descriptive research methods with a qualitative approach. Data collection techniques used were interviews with 4 speakers. The data analysis technique used is the first data reduction, data presentation, an d drawing conclusions. Based on the results of research conducted by the author, it can be concluded that the level of tax compliance in Kertajatis subdistrict is relatively obedient, it's just that the services performed by the tax apparatus are less than optimal and still cause some problems among the people (taxpayers).